The factors that influence the volatility of crude oil’s price / Nabila Huda Ahmad - Ahmad, Nabila Huda (2014)
The objective of this paper is to examine the factor that effects of crude oil price in Malaysia, using monthly data from 2004 to 2012. The software that used to analyze the data is called STATA (Statistics/Data analysis). This finding will contribute to Malaysian government in making policy to control the petrol price to avoid from the inflation. There are many factors that contribute to this situation. Many previous researches were conducted to identify the relationship between these factors with Crude Oil’s price. In this research, I will discuss the three factors that may influencing the volatility of Crude Oil’s price which are crude palm oil’s price, exchange rate, and interest rate.